2021
DOI: 10.1002/cncr.33402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of provider type and number of providers on surveillance testing among survivors of head and neck cancers

Abstract: BACKGROUND: Guidelines for follow-up after head and neck cancer (HNC) treatment recommend frequent clinical examinations and surveillance testing. Here, the authors describe real-world follow-up care for HNC survivors and variations in surveillance testing. METHODS: Using Surveillance, Epidemiology, and End Results (SEER)-Medicare data, this study examined a population-based cohort of HNC survivors between 2001 and 2011 Usage of cross-sectional head and neck imaging (CHNI), chest imaging (CI), positron emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recent work on HNC survivorship utilization specifically has shown that care utilization can vary widely between patients, can be bolstered by a survivor's involvement (cancer-related or otherwise) with primary care, and frequently decreases over time. 16,17 This research reveals the patterns of those who engage in survivorship care but cannot provide insight into the experience of those who, for whatever reason, do not. As a complement to work on HNC survivorship care utilization, our findings are a first step toward a detailed understanding of how best to meet the needs of all HNC survivors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent work on HNC survivorship utilization specifically has shown that care utilization can vary widely between patients, can be bolstered by a survivor's involvement (cancer-related or otherwise) with primary care, and frequently decreases over time. 16,17 This research reveals the patterns of those who engage in survivorship care but cannot provide insight into the experience of those who, for whatever reason, do not. As a complement to work on HNC survivorship care utilization, our findings are a first step toward a detailed understanding of how best to meet the needs of all HNC survivors.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is concordant with those reported by others. Massa et al, 24 in a prospective cross‐sectional survey study, identified multidisciplinary care as a factor associated with a desire for more frequent follow‐up visits, and Yao et al, 16 in a retrospective study based on Surveillance, Epidemiology, and End Results–Medicare, found that the treatment received was associated with HNC patients' follow‐up care utilization. Multimodality cancer treatment correlates with higher stage cancer, greater treatment complexity, and more severe treatment toxicity—all of which are factors that reasonably might result in survivor needs that could be addressed through continued survivorship care.…”
Section: Discussionmentioning
confidence: 99%
“…The BDI is a widely used and well-validated measure of depressive symptomatology consisting of 21 items scored 0-3, each assessing a unique category of depressive symptoms. 18 Cutoff scores have been established which suggest minimal (0-9), mild (10)(11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe (30-63) depression. 18 The BDI has been used in both nonclinical and clinical samples, including those with HNC.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…While exploration of these factors is needed, research also demonstrates that utilization of follow‐up care declines with time. 10 , 12 One recent study found that only half of patients receive recommended surveillance testing over a 2‐year period posttreatment, for example. 12 Limited research to date suggests that factors such as marital status, treatment modality, and poor recognition of the recommended follow‐up period may be related to discontinuation in HNC, 8 , 9 but overall extremely little is known about those who discontinue follow‐up care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation